Feasibility of Developing Creative Mathematics Learning Media Augmented Reality Building Materials - Sukriadi, Sukriadi; Kusdar, Kusdar; Djangka, La; Muhlis, Muhlis; Febiola, Dyna; Agus Salim, Nur (Technium Social Sciences Journal, 2023)
This study aims to determine the feasibility of Augmented Reality Creative Mathematics learning media for geometric materials in elementary schools. The development of Augmented Reality Creative Mathematics learning media uses research and development methods or Research & Development, which produces a three-dimensional learning media using Augmented Reality technology in the Assemblr Edu application. This research and development use the ADDIE development model, which includes 5 development steps, namely: 1) analysis, namely needs analysis; 2) design, namely design or planning; 3) development, namely development; 4) implementation, namely implementation and 5) evaluation, namely evaluation. Based on the feasibility test results, it can be concluded that the Augmented Reality Creative Mathematics media is suitable for use as a learning medium for geometric materials in class V SDIT Istiqamah Balikpapan.